Transformational Leadership as a Catalyst for Innovation and Quality in Education: A Literature Review - M. Makhrus Ali; Ubaidillah; Khomsinnudin; Ismawati (Journal of Innovative and Creativity, 2025)
In an era marked by globalization and technological upheaval, the education sector faces complex challenges that require adept leadership strategies to drive progress and improve educational standards. The purpose of this investigation is to examine the importance of transformational leadership as a catalyst for driving innovation and improving quality in contemporary education, as evidenced by a comprehensive review of the relevant literature. Using a research approach grounded in a literature review, this study explores existing academic work, particularly across the spectrum of primary to post-secondary education. Through thematic analysis, common patterns and motifs are identified. The findings of this investigation demonstrate the efficacy of transformational leadership in driving educational innovation, enhancing educational experiences, and strengthening the resilience of educational institutions. Leaders who are proficient in transformational strategies demonstrate greater efficacy in assimilating new technologies, fostering environments conducive to ingenuity, and facilitating adaptation to rapid transformations in the education sector.